The Banker's Oath And Financial Advice - Utz Weitzel; Michael Kirchler (Tinbergen Institute, 2021)
Financial misbehavior is widespread and costly. The Dutch government legally requires every employee in the financial sector to take a Hippocratic oath, the so-called ``banker's oath.'' We investigate whether moral nudges that directly and indirectly remind financial advisers of their oath affect their service. In a large-scale audit study, professional auditors confronted 201 Dutch financial advisers with a conflict of interest. We find that when auditors apply a moral nudge, referring to the banker's oath, advisers are less likely to prioritize bank's interests. In additional prediction tasks, we find that Dutch regulators expect stronger effects of the oath than observed.
Keywords: C92; D84; G02; G14; 330; experimental finance; audit study; banker's oath; moral nudges; financial advice